Factors that Influence Food Waste at the Istiqomah Samarinda Islamic Boarding School - Muhammad Faisal; Wiryanto; Riana Pangestu Utami (PT FORMOSA CENDEKIA GLOBAL, 2023)
Food waste is an indicator of the success of nutrition services in hospitals or other institutions. The failure and success of food service can be seen from the remaining food served. Food waste on plates is quantitative data that can be used to evaluate nutrition education programs. This research uses a quantitative approach based on the use of data in the form of numbers as a tool for analyzing variable measurements and drawing conclusions from the phenomena studied. This type of research is analytical observation with a cross-sectional design. The population in this study were students and female students at the Istiqomah Samarinda Islamic Boarding School class VII, totaling 54 people, consisting of 25 female students, while there were 29 female students.